Characterization of Fungal and Bacterial Components in Gut/Fecal Microbiome - Kirschner, Roland; Hsu, Tien; Ngoc Tuan, Nguyen; Chen, Chien-Lung; Huang, Shir-Ly (Current Drug Metabolism, 2015)
The gut microbiota is a complex ecosystem that affects the development, nutritional status and immunological responses of the host. Prokaryotes and fungi in the community have the abilities to withstand the adverse conditions of high temperature, low oxygen etc. and to decompose complex organic molecules. The novel approaches of metagenomics and metaproteomics provide data that allow the detection of patterns of constancy or changes in time or under different conditions, such as different diets, disease condition and antibiotic therapy. These large-scale patterns can be correlated with certain health or disease conditions. From the organismic point of view, however, the species identity of the organisms and their interactions in the gut and how these interactions influence the prevention or development of disease are poorly known. The diversity and roles of fungi in animal feces appear to be better known than in human gut/feces. A combined compilation of the diverse methods applied towards prokaryotes and fungi in the gut/feces microbiome serves as a base for meeting the challenges of masses of large-scale datasets on the one hand and lack of substantial organismic understanding on the other. Starting from long-term monitoring and large-scale characterization of the composition of microbiome from systematic higher groups down to the genus level, microbial genomes and proteomes, particular key components with antimicrobial or immune functions can be selected and investigated in detail with respect to understanding of host-microbiota interaction, disease pathogenesis and developing diagnostic and therapeutic tools.
Keywords: gut